PEMBERDAYAAN KELOMPOK WANITA TANI MELALUI PEMANFAATAN LAHAN PEKARANGAN UNTUK BUDIDAYA SAYURAN SEHAT DI KECAMATAN BOJONGGAMBIR KABUPATEN TASIKMALAYA - M. Sholehuddin Al Ayyubi; Yul Harry Bahar; Achmad Musyadar (Universitas Muhammadiyah Mataram, 2021)
Empowerment of Women Farmers Groups (KWT) through the utilization of yardland is one way to improve the quality of life and women's independence. The purpose of the study is to describe, analyze, and formulate a strategy for empowering KWT through the use of yard land for healthy vegetable cultivation in Bojonggambir District, Tasikmalaya Regency. The number of samples was determined by the total sampling method. The results of descriptive analysis describe the characteristics of KWT on age (productive), education (low), length of farming (high), yard area (narrow), and all external factors (medium). The related factors are the area of the yard, the role of agricultural extension workers, and the availability of facilities and infrastructure. The strategy is in the form of extension activities with descriptive analysis to determine the material and Spearman Rank correlation to optimize factors related to empowerment, namely the area of yards (sig .044), availability of facilities and infrastructure (sig .037), and the role of extension workers (sig .000).